3(2x-6)=6(2x+1)

Simple and best practice solution for 3(2x-6)=6(2x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x-6)=6(2x+1) equation:


Simplifying
3(2x + -6) = 6(2x + 1)

Reorder the terms:
3(-6 + 2x) = 6(2x + 1)
(-6 * 3 + 2x * 3) = 6(2x + 1)
(-18 + 6x) = 6(2x + 1)

Reorder the terms:
-18 + 6x = 6(1 + 2x)
-18 + 6x = (1 * 6 + 2x * 6)
-18 + 6x = (6 + 12x)

Solving
-18 + 6x = 6 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
-18 + 6x + -12x = 6 + 12x + -12x

Combine like terms: 6x + -12x = -6x
-18 + -6x = 6 + 12x + -12x

Combine like terms: 12x + -12x = 0
-18 + -6x = 6 + 0
-18 + -6x = 6

Add '18' to each side of the equation.
-18 + 18 + -6x = 6 + 18

Combine like terms: -18 + 18 = 0
0 + -6x = 6 + 18
-6x = 6 + 18

Combine like terms: 6 + 18 = 24
-6x = 24

Divide each side by '-6'.
x = -4

Simplifying
x = -4

See similar equations:

| 4+8=48 | | 6+6*6-6+6= | | f(x)=4x^2-1/9x^2-1 | | 6+6.6-6+6= | | 4=5/ | | x^2-12x+6=-30 | | 5x^2+20x+25=10 | | kx^2-(3k+1)x-15=0 | | kx^2+(3k-1)x-15=0 | | 5x^2-10x-70=5 | | =3-n | | =2n+1 | | 1/x-1/4=2/x | | x^2-2x-8=-7 | | 4x^2-8x-84=8 | | x^2+10x+12=3 | | =5n-20 | | 8m-15=9m+12 | | 1/4m-2m | | 4(x)-3=y | | 5(3-r)+2=3(r+2) | | -4x+21=3x | | -7x+4=2x-5 | | -8x-1=x+26 | | -4x-9=x+1 | | -3w+5=7w-3 | | 12x^4-4x^2-5=0 | | -3x+8=x-4 | | 2a+17=6a+5 | | -3u+10=5u+3 | | 5x+1=12-x | | 5p+1=3p+13 |

Equations solver categories